Both hypophosphatemia and hyperphosphatemia are associated with increased mortality in septic patients - Liu, Zheng; Li, Teng; Du, Yihan; Li, Chenhu; Chong, Wei (Frontiers in Nephrology, 2022)
Objective: This study was intended to explore the relationship between level of serum phosphate and prognosis in septic patients. Methods: Data were obtained from the public database, which were divided into 2 subgroups according to whether they were complicated with chronic kidney disease. Initial values of serum phosphate were extracted from patients on admission to hospital. Propensity score-matched analysis was performed and the relationship between hypophosphatemia and hyperphosphatemia and the severity of the disease in septic patients was explored separately. The lowess smoothing technique and the Kaplan-Meier method were utilized for a preliminary analysis of serum phosphate levels in relation to in-hospital mortality and 28-day survival. The initial values of serum phosphate were graded as level 1 (<1.5 mg/dL), level 2 (1.5-2.7 mg/dL), level 3 (2.7-4.5 mg/dL), level 4 (4.5-5.5 mg/dL), level 5 (5.5-6.5 mg/dL), level 6 (6.5-7.5 mg/dL)) and level 7 (> 7.5 mg/dL). Multivariate logistic regression and cox regression was used to analyse the relationship between serum phosphate levels and mortality. Results: 4059 cases (17.4%) were combined with chronic kidney disease, of which 419 (10.3%) were hypophosphatemia and 1091 (26.8%) were hyperphosphatemia. 19224 cases (82.6%) were not combined with chronic kidney disease, of which 3769 (19.6%) were hypophosphatemia and 2158 (11.2%) were hyperphosphatemia. After propensity score-matched, in-hospital mortality, 28-day mortality, risk of septic shock was significantly higher in the 2 subgroups of hypophosphatemia patients than in normophosphatemia patients. In-hospital mortality, 28-day mortality, risk of septic shock, occurrence of renal replacement therapy, occurrence of acute renal failure, and maximum clinical score were all significantly higher in the 2 subgroups of patients with hyperphosphatemia than in patients with normophosphatemia. Multivariate logistic regression was consistent with Cox regression results. In septic patients without chronic kidney disease, hypophosphatemia was an independent risk factor for death, the lower the serum phosphate, the greater the risk of death. In all septic patients, hyperphosphatemia was an independent risk factor for death, the higher the serum phosphate, the greater the risk of death. Conclusions: Both hypophosphatemia and hyperphosphatemia are associated with increased mortality in septic patients and are independent risk factors for death.